Asymmetric introgression of African genes in honeybee populations (Apis mellifera L.) in Central Mexico - (:unkn) unknown (My University, 2007)
The Africanization of the honeybee (Apis mellifera) in South America is one of the most spectacular examples of biological invasions. In this study, we analyzed the Africanization process in Central Mexico along an altitudinal transect from 72 to 2800 m, using both mitochondrial and nuclear DNA markers. The mitochondrial analysis revealed that the two high-altitude populations had a significantly greater percentage of African mitotypes (95%) than the three lowland populations (67%), indicating successful spreading of Africanized swarms to these altitudes. All populations (highland and lowland) had a similar overall proportion of African alleles at nuclear loci (58%). Thus, all populations showed an asymmetric introgression of African nuclear and mtDNA. Colonies with African mitotypes had, on average, significantly more African nuclear alleles (60%) than those with European mitotypes (51%). Furthermore, the three lowland populations showed clear signs of linkage disequilibrium, while the two high-altitude populations did not, indicating recent genetic introgression events into the lowland populations.
Keywords: African Research